THE EFFECT OF THE OREM MODEL APPROACH ON KNOWLEDGE AND ATTITUDE OF PREGNANT WOMEN IN REDUCING THE INCIDENCE OF SEVERE PREECLAMPSIA (PEB) DURING THE PANDEMIC - Azizah, Salmaa Nur; Ambarsari, Wulan Novika; Oktri, Yosi (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2023)
Background : One of the causes of maternal death is preeclampsia, the high incidence of preeclampsia in Indonesia cannot be separated by several factors such as low education and lack of health awareness. The role of nurses in this case: is to carry out promotive efforts by carrying out health promotions to pregnant women about preeclampsia, Self Care Orem theory with the main focus on seeing how a person maintains his health and welfare can be applied through health education as an effort to increase knowledge and attitudes of pregnant women. Objectives : This study aims to determine the effect of the Orem model approach on the knowledge and attitudes of pregnant women about preeclampsia at the North Cimahi Health Center. Methods : This research method is quasi-experimental quantitative research with a one-group pretest-posttest design. The sample is 55 respondents using the purposive sampling technique. The instrument is a knowledge and attitude questionnaire about preeclampsia. Result : The results of this study indicate that half of them, 30 respondents (54.4%) have good knowledge and almost all 46 respondents (83.6%) have a positive attitude. Based on the analysis of the Marginal Homogeniety and Mcnemar test, the value of p = 0.000 < (0.05). Conclusions : Concluded that there is an effect of the Orem model approach on the knowledge and attitudes of pregnant women regarding preeclampsia. The results of this study are expected to be used as a reference and basis for improving the health status of pregnant women, especially in preventing preeclampsia.